Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's use algebraic identities to find each of the given products step-by-step.
### (i) [tex]\((x+5)(x+2)\)[/tex]
To find the product of [tex]\((x+5)(x+2)\)[/tex], we use the distributive property (also known as the FOIL method in this case):
[tex]\[ (x+5)(x+2) = x \cdot x + x \cdot 2 + 5 \cdot x + 5 \cdot 2 \][/tex]
Simplifying each term:
[tex]\[ = x^2 + 2x + 5x + 10 \][/tex]
Combine the like terms ([tex]\(2x + 5x\)[/tex]):
[tex]\[ = x^2 + 7x + 10 \][/tex]
So, the result is:
[tex]\[ (x+5)(x+2) = x^2 + 7x + 10 \][/tex]
### (ii) [tex]\((x-5)(x-5)\)[/tex]
This product represents the square of a binomial. We use the identity [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[ (x-5)^2 = x^2 - 2 \cdot x \cdot 5 + 5^2 \][/tex]
Simplifying the terms:
[tex]\[ = x^2 - 10x + 25 \][/tex]
So, the result is:
[tex]\[ (x-5)(x-5) = x^2 - 10x + 25 \][/tex]
### (iii) [tex]\((3x+2)(3x-2)\)[/tex]
This product represents the difference of squares. We use the identity [tex]\((a+b)(a-b) = a^2 - b^2\)[/tex]:
[tex]\[ (3x+2)(3x-2) = (3x)^2 - (2)^2 \][/tex]
Simplifying the terms:
[tex]\[ = 9x^2 - 4 \][/tex]
So, the result is:
[tex]\[ (3x+2)(3x-2) = 9x^2 - 4 \][/tex]
### (iv) [tex]\(\left(x^2 + \frac{1}{x^2}\right)\left(x^2 - \frac{1}{x^2}\right)\)[/tex]
This product also represents the difference of squares, where [tex]\(a = x^2\)[/tex] and [tex]\(b = \frac{1}{x^2}\)[/tex]:
[tex]\[ \left(x^2 + \frac{1}{x^2}\right)\left(x^2 - \frac{1}{x^2}\right) = (x^2)^2 - \left(\frac{1}{x^2}\right)^2 \][/tex]
Simplifying the terms:
[tex]\[ = x^4 - \frac{1}{x^4} \][/tex]
So, the result is:
[tex]\[ \left(x^2 + \frac{1}{x^2}\right)\left(x^2 - \frac{1}{x^2}\right) = x^4 - \frac{1}{x^4} \][/tex]
### (v) [tex]\((1+x)(1+x)\)[/tex]
This product represents the square of a binomial. We use the identity [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex]:
[tex]\[ (1 + x)^2 = 1^2 + 2 \cdot 1 \cdot x + x^2 \][/tex]
Simplifying the terms:
[tex]\[ = 1 + 2x + x^2 \][/tex]
So, the result is:
[tex]\[ (1+x)(1+x) = 1 + 2x + x^2 \][/tex]
By following these steps and using the appropriate algebraic identities, we have computed the given products accurately.
### (i) [tex]\((x+5)(x+2)\)[/tex]
To find the product of [tex]\((x+5)(x+2)\)[/tex], we use the distributive property (also known as the FOIL method in this case):
[tex]\[ (x+5)(x+2) = x \cdot x + x \cdot 2 + 5 \cdot x + 5 \cdot 2 \][/tex]
Simplifying each term:
[tex]\[ = x^2 + 2x + 5x + 10 \][/tex]
Combine the like terms ([tex]\(2x + 5x\)[/tex]):
[tex]\[ = x^2 + 7x + 10 \][/tex]
So, the result is:
[tex]\[ (x+5)(x+2) = x^2 + 7x + 10 \][/tex]
### (ii) [tex]\((x-5)(x-5)\)[/tex]
This product represents the square of a binomial. We use the identity [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[ (x-5)^2 = x^2 - 2 \cdot x \cdot 5 + 5^2 \][/tex]
Simplifying the terms:
[tex]\[ = x^2 - 10x + 25 \][/tex]
So, the result is:
[tex]\[ (x-5)(x-5) = x^2 - 10x + 25 \][/tex]
### (iii) [tex]\((3x+2)(3x-2)\)[/tex]
This product represents the difference of squares. We use the identity [tex]\((a+b)(a-b) = a^2 - b^2\)[/tex]:
[tex]\[ (3x+2)(3x-2) = (3x)^2 - (2)^2 \][/tex]
Simplifying the terms:
[tex]\[ = 9x^2 - 4 \][/tex]
So, the result is:
[tex]\[ (3x+2)(3x-2) = 9x^2 - 4 \][/tex]
### (iv) [tex]\(\left(x^2 + \frac{1}{x^2}\right)\left(x^2 - \frac{1}{x^2}\right)\)[/tex]
This product also represents the difference of squares, where [tex]\(a = x^2\)[/tex] and [tex]\(b = \frac{1}{x^2}\)[/tex]:
[tex]\[ \left(x^2 + \frac{1}{x^2}\right)\left(x^2 - \frac{1}{x^2}\right) = (x^2)^2 - \left(\frac{1}{x^2}\right)^2 \][/tex]
Simplifying the terms:
[tex]\[ = x^4 - \frac{1}{x^4} \][/tex]
So, the result is:
[tex]\[ \left(x^2 + \frac{1}{x^2}\right)\left(x^2 - \frac{1}{x^2}\right) = x^4 - \frac{1}{x^4} \][/tex]
### (v) [tex]\((1+x)(1+x)\)[/tex]
This product represents the square of a binomial. We use the identity [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex]:
[tex]\[ (1 + x)^2 = 1^2 + 2 \cdot 1 \cdot x + x^2 \][/tex]
Simplifying the terms:
[tex]\[ = 1 + 2x + x^2 \][/tex]
So, the result is:
[tex]\[ (1+x)(1+x) = 1 + 2x + x^2 \][/tex]
By following these steps and using the appropriate algebraic identities, we have computed the given products accurately.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.